The Esg Gene Is Involved in Nicotine Sensitivity in Drosophila melanogaster. - Sanchez-Díaz, I.; Rosales-Bravo, F.; Reyes-Taboada, J.L.; Covarrubias, A.A.; Narvaez-Padilla, V.; Reynaud, E. (PLoS ONE, 2015)
In humans, there is a strong correlation between sensitivity to substances of abuse and addiction risk. This differential tolerance to drugs has a strong genetic component. The identification of human genetic factors that alter drug tolerance has been a difficult task. For this reason and taking advantage of the fact that Drosophila responds similarly to humans to many drugs, and that genetically it has a high degree of homology (sharing at least 70% of genes known to be involved in human genetic diseases), we looked for genes in Drosophila that altered their nicotine sensitivity. We developed an instantaneous nicotine vaporization technique that exposed flies in a reproducible way. The amount of nicotine sufficient to "knock out" half of control flies for 30 minutes was determined and this parameter was defined as Half Recovery Time (HRT). Two fly lines, L4 and L70, whose HRT was significantly longer than control´s were identified. The L4 insertion is a loss of function allele of the transcriptional factor escargot (esg), whereas L70 insertion causes miss-expression of the microRNA cluster miR-310-311-312-313 (miR-310c). In this work, we demonstrate that esg loss of function induces nicotine sensitivity possibly by altering development of sensory organs and neurons in the medial section of the thoracoabdominal ganglion. The ectopic expression of the miR-310c also induces nicotine sensitivity by lowering Esg levels thus disrupting sensory organs and possibly to the modulation of other miR-310c targets.